Systematic differences in online reviews of hotel services between business and leisure travelers. (April 2023) - Kim, Jong Min; Ma, Haoxiang; Park, Sungjun (Steven)
To understand whether the purpose of travel affects differences in the evaluation of hotel services, we analyzed online reviews for 768 hotels in New York City. The results show that leisure travelers are predisposed to leaving online reviews with higher ratings and positive emotions than those posted by business travelers, while the latter's review ratings are more widely dispersed, indicating greater inconsistency in their evaluations of hotel services. Based on our empirical evidence about systematic differences in online reviews of hotel services between business and leisure travelers, we can provide the hospitality industry with meaningful business implications.